Processed multichannel seismic data off the eastern Greenland margin acquired during the Robert D. Conrad expedition RC2412 (1983) (IEDA: Marine-Geo Digital Library, 2019)
A collaborative effort between LDEO and BGR, this was a two-ship survey. R/V Conrad and S/V Prospekta collected COP and ESP data on the Norwegian margin. S/V Prospekta was the lead ship during COPs for all lines. The primary objective was to obtain data on both sides of the conjugate margins with which to study the dipping reflectors and structures. A companion cruise, RC2411, obtained data on the Norwegian side. Funding was from NSF Grant OPP-8216014.